2009
DOI: 10.1111/j.1365-2567.2009.03134.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumour‐derived prostaglandin E2 and transforming growth factor‐β synergize to inhibit plasmacytoid dendritic cell‐derived interferon‐α

Abstract: SummaryIn previous studies we reported that plasmacytoid dendritic cells (PDC) infiltrating head and neck cancer tissue are functionally impaired, but the molecular basis for the functional deficiency remained unclear. Here we demonstrate that tumour-derived prostaglandin E2 (PGE 2 ) and transforming growth factor-b (TGF-b) increase interleukin-8 (IL-8) but synergistically inhibit interferon-a (IFN-a) and tumour necrosis factor (TNF) production of Toll-like receptor 7 (TLR7)-and Toll-like receptor 9 (TLR9)-sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
61
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 53 publications
6
61
1
Order By: Relevance
“…The inhibitory role of TGF-b is consistent with a previous study showing that increased intratumoral IFN-a levels correlates with reduced TGF-b1 in breast cancer patients (33). Moreover, recent reports in mice and human showed that this cytokine contributes to peyer patches, splenic stromal, and tumor environments mediated inhibition of pDC capacity to produce IFN-a (29,34,35). The deleterious prognostic effect of TApDC in ovarian cancer could be related to the alteration of IFN-a production.…”
Section: Discussionsupporting
confidence: 77%
“…The inhibitory role of TGF-b is consistent with a previous study showing that increased intratumoral IFN-a levels correlates with reduced TGF-b1 in breast cancer patients (33). Moreover, recent reports in mice and human showed that this cytokine contributes to peyer patches, splenic stromal, and tumor environments mediated inhibition of pDC capacity to produce IFN-a (29,34,35). The deleterious prognostic effect of TApDC in ovarian cancer could be related to the alteration of IFN-a production.…”
Section: Discussionsupporting
confidence: 77%
“…Incubation of monocytes with the cyclooxygenase inhibitor indomethacin partially reduced the ability of monocyte-derived supernatants to inhibit PDC function, suggesting that in addition to IL-10, cyclooxygenasedependent formation of PGs contributes to inhibition of PDCs. Consistent with this finding, tumor-derived PGs were found to inhibit the ability of PDCs to produce IFN-a upon stimulation with CpG DNA (33).…”
Section: Discussionsupporting
confidence: 72%
“…PGE 2, secreted mostly by the pigment epithelium, is widely recognized as an inflammatory molecule in the eye. At the same time, it is widely accepted that PGE 2 also helps to explain the immune escape of cancer by inhibiting maturation of the DC [14]. In this study, we first confirmed the immunosuppressive effects of TGF-b 2 on LPS-induced maturation of DC.…”
Section: Introductionsupporting
confidence: 89%